The CRISPR-Cas Mechanism for Adaptive Immunity and Alternate Bacterial Functions Fuels Diverse Biotechnologies - Newsom, Sydney; Parameshwaran, Hari Priya; Martin, Lindsie; Rajan, Rakhi (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial and archaeal CRISPR-Cas systems offer adaptive immune protection against foreign mobile genetic elements (MGEs). This function is regulated by sequence specific binding of CRISPR RNA (crRNA) to target DNA/RNA, with an additional requirement of a flanking DNA motif called the protospacer adjacent motif (PAM) in certain CRISPR systems. In this review, we discuss how the same fundamental mechanism of RNA-DNA and/or RNA-RNA complementarity is utilized by bacteria to regulate two distinct functions: to ward off intruding genetic materials and to modulate diverse physiological functions. The best documented examples of alternate functions are bacterial virulence, biofilm formation, adherence, programmed cell death, and quorum sensing. While extensive complementarity between the crRNA and the targeted DNA and/or RNA seems to constitute an efficient phage protection system, partial complementarity seems to be the key for several of the characterized alternate functions. Cas proteins are also involved in sequence-specific and non-specific RNA cleavage and control of transcriptional regulator expression, the mechanisms of which are still elusive. Over the past decade, the mechanisms of RNA-guided targeting and auxiliary functions of several Cas proteins have been transformed into powerful gene editing and biotechnological tools. We provide a synopsis of CRISPR technologies in this review. Even with the abundant mechanistic insights and biotechnology tools that are currently available, the discovery of new and diverse CRISPR types holds promise for future technological innovations, which will pave the way for precision genome medicine.